Serotype distribution and antimicrobial susceptibility of Streptococcus suis isolates from porcine diagnostic samples in Hungary, 2020–2023 - Ervin Albert; István Emil Kis; Krisztián Kiss; Katalin K-Jánosi; Tamás Révész; Imre Biksi (Porcine Health Management)
Abstract Background Streptococcus suis (S. suis) is a major swine pathogen and a significant zoonotic agent, causing substantial economic losses in the swine sector and having considerable public health importance. The control and management of S. suis-related conditions has become increasingly challenging due to the multitude of involved serotypes with varying antimicrobial resistance patterns. Here, we report the serological distribution and antimicrobial susceptibility of S. suis isolates isolated form clinical samples of Hungarian large-scale swine farms. Results Between 2020 and 2023, altogether 296 S. suis isolates were obtained from diseased pigs of 64 Hungarian pig operations. Serotyping of the isolates was carried out by using molecular methods (cps-typing). The isolated strains belonged to 24 single cps-types. The most frequently detected cps-types during the four years of this passive survey were 9 (19.6%), 2 (19.3%), 1/2 (18.9%) and 7 (14.5%). The brain, spleen, endocardial valve thrombus and lung proved to be the most frequent site of S. suis strain isolation, and animals 29–75 days of age were affected in the highest proportion. Antimicrobial susceptibility testing of the isolates was performed by determining the minimal inhibitory concentration for 15 antimicrobial agents of veterinary and human importance using a commercial microdilution assay. More than 90% of the tested isolates proved to be susceptible to the examined beta-lactams, cephalosporins and florfenicol, as well as to rifampicin, trimethoprim/sulfamethoxazole and vancomycin. Phenotypic resistance profiles (resistotypes) of clindamycin-tetracyclin (3.8%), clindamycin-erythromycin-tetracyclin (8.4%) and clindamycin-erythromycin-tetracyclin-trimethoprim / sulfamethoxazole (3.8%) were most frequently detected. Vancomycin resistance was observed in the case of 1 S. suis strain. Conclusions The dominance of S. suis cps-types 9, 2, 1/2 and 7 in Hungary over the four years of this study aligns with previous reports from several countries worldwide. The presence of highly susceptible S. suis isolates suggests a prudent antibiotic usage and treatment practice in the surveyed Hungarian swine operations. In contrary, the presence of several resistotypes could indicate the problem of antibiotic resistance in the future.